Optimizing sharia banking business Units financial performance through effective risk management - Halim, Sofyan (Edelweiss Applied Science and Technology, 2025)
This study aims to conduct research on the impact of financial arrangements, operational costs, and risk management practices as intervening factors on financial performance in Sharia Banking Business Units in Indonesia. This study explores the complex relationship between the financing framework and operational efficiency over operational investment. Additionally, this study examines the relationship between risk management practices and financial results. This research contributes substantively to the development of Islamic finance. The integration of Non-Performing Financing variables and the duration of the research, which spans from 2014 to 2024, provides strategic insights and enriches the depth of analysis. The distinguishing feature of this study is its concentrated focus on Sharia Banking Business Units and risk management variables as intervening factors, facilitating a comprehensive analysis. This study employs multiple linear regression analysis to assess the effect of risk management mediation on the relationship between operational efficiency and financial performance. The results of the study highlight the importance of operational efficiency and risk management in improving financial performance. Empirical evidence corroborates a significant correlation between financing strategies and the relationship between operational efficiency, risk management, and financial outcomes. Furthermore, this study supports a theoretical framework that interconnects these variables, ensuring that the results of the analysis have direct and indirect implications for risk management variables as intervening factors, while offering significant insights for policymakers and practitioners involved in the domain of Sharia Banking Business Units.